OPTIMALISASI STRATEGI PROMOSI UMKM DESA BURAI MELALUI PEMANFAATAN APLIKASI DIGITAL - Yunita, Dessy; Nofiawaty, Nofiawaty; Iisnawati, Iisnawati (Jurnal AbdiMas Nusa Mandiri, 2026)
In the digital era, online business has become dominant but has not completely replaced offline enterprises. The integration of online and offline strategies provides a more effective approach to enhancing customer experience and business growth. Desa Burai, Ogan Ilir, Sumatra Selatan, has significant human resource potential as business owners; however, this is not followed by adequate marketing capabilities, particularly in terms of promotional activities, which remain largely traditional. The participants of this Community Service Program consisted of 25 local business owners who had never or had only minimally engaged in digital advertising. The objective of this program was to introduce Canva, a user-friendly graphic design platform, to help business owners create simple digital-based advertisements. Canva enables participants to develop advertising materials as an effort to optimize promotional strategies. The methods implemented in this program included an initial survey, training activities, and post-activity evaluation. The results indicated an improvement in business owners’ ability to market their products more broadly within the digital context.